Peran Pendidikan Keluarga Dalam Pembinaan Moral Remaja Menghadapi Era Globalisasi - Djauharah Bawazir; R. Santoso Murwani; Sri Hastuti Suryotomo; Yusriah Nasution; Endri Buriswati (Universitas Negeri Malang, 2016)
This is a descriptive explorative research that studies the role of family education in developing the morality of youth in facing the global era. This study is conducted at 5 sub-districts in DKI and the sample is SMA students in the sub-districts of DKI. The technique of analysis employed is the Pearson Product Moment Coorelation. The result of the correlational analysis reveals that he role of family education is not significant. However, from the description of data it is found out that family education affects positively on the development of the morality of the youth.